Three-layer core-shell structure oxygen evolution catalyst and preparation method and application thereof

CN117328096BActive Publication Date: 2026-10-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311275316.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2026-10-16
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

[0004]鉴于此,本发明的目的在于提供一种三层核壳结构析氧催化剂及其制备方法与应用,以解决当前PEM电解水制氢所用析氧催化剂存在的贵金属使用量高和稳定性不够的问题,本发明利用Pt和/或Au贵金属次外层包覆非贵金属内核可以解决内核非贵金属易被腐蚀的问题;进一步,利用上述贵金属包覆非贵金属内核作为高析氧活性物的载体,可以减少贵金属Ir使用量;由于次外层Pt和/或Au元素仅几个原子厚,用量也极低,所以整个催化剂的贵金属使用量较无载体的商业氧化铱催化剂明显降低,而且稳定性也得到了保证

Benefits of technology

[0029](1) The three-layer core-shell structure oxygen evolution catalyst of the present invention uses relatively inexpensive non-precious metals for the core, which can reduce the amount of precious metals used and help reduce the cost of oxygen evolution catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117328096B_ABST
    Figure CN117328096B_ABST
Patent Text Reader

Abstract

The application discloses a three-layer core-shell structure oxygen evolution catalyst and a preparation method and application thereof, and belongs to the technical field of hydrogen production by water electrolysis. The inner core of the three-layer core-shell structure oxygen evolution catalyst is a non-noble transition metal (one or more than two of Ti, Cu, Co, Ni, Cr, Ta and Nb), the secondary outer layer is a few atomic layers of a dense noble metal (one or two of Au and Pt), and the outermost layer is an iridium oxyhydroxide with high oxygen evolution activity. The application uses a relatively inexpensive non-noble metal as the inner core, so that the use amount of the noble metal can be reduced; the secondary outer layer of the noble metal is used to coat the inner core, so that the inner core element can be protected from being dissolved, and a good electron conduction path can be provided for the outermost oxygen evolution active component; and the three-layer core-shell structure catalyst of the application is used as an oxygen evolution catalyst, so that the stability can be maintained while the use amount of the noble metal is reduced, and the cost of PEM water electrolysis hydrogen production can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis for hydrogen production technology, and relates to a three-layer core-shell structure oxygen evolution catalyst for water electrolysis for hydrogen production, its preparation method and application. Background Technology

[0002] Hydrogen energy is considered the most promising energy carrier to replace traditional fossil fuels. Compared with other energy sources, hydrogen has a high calorific value (140 MJ / kg), which is 3.26 times that of crude oil, 3.87 times that of natural gas, and 5.19 times that of coke. Furthermore, its combustion product is water, making it a recognized clean energy source. Given the current severe curtailment of wind and solar power in my country, using electricity generated from wind and solar renewable energy sources to electrolyze water for hydrogen production has significant economic value. In recent years, proton exchange membrane (PEM) water electrolysis technology has become a research hotspot in the field of water electrolysis for hydrogen production due to its advantages such as high efficiency, zero emissions, compact structure, environmental friendliness, and high product purity. However, PEM water electrolysis for hydrogen production still faces problems such as high cost and small scale, limiting its industrial application. Currently, the oxygen evolution catalyst at the anode in PEM water electrolysis for hydrogen production heavily relies on the precious metal Ir. Since a suitable support is unavailable, the amount of Ir used is inevitably very high, which is one of the important reasons for the high cost of PEM water electrolysis for hydrogen production. Currently, commercially available iridium oxide catalysts are supportless, pure noble metal-based oxygen evolution catalysts, and their oxygen evolution activity is generally low. To achieve a considerable current density (typically 1.0-3.0 A / cm²), further research is needed. 2 High loading (typically 1.0-5.0 mg / cm³) is required in PEM electrolytic membrane electrodes. 2 The use of iridium oxide catalysts results in persistently high operating costs. Therefore, it is necessary to develop supported oxygen evolution catalysts that can reduce the amount of precious metal Ir used while maintaining good oxygen evolution activity and stability, thereby reducing the cost of PEM water electrolysis for hydrogen production.

[0003] In existing technologies, some methods use non-precious metals to form alloys with Ir to reduce Ir usage. However, during long-term operation, the non-precious metals will eventually be lost in the oxygen evolution environment, causing the alloy structure to fail. Moreover, the contribution of alloying to reducing Ir usage is relatively limited. Some methods directly use non-precious metals as the core and Ir as the shell to construct core-shell catalysts. This method is beneficial for reducing Ir usage. However, as the shell Ir gradually dissolves during the oxygen evolution process, the exposed core non-precious metal will be rapidly corroded, causing the entire core-shell structure to collapse and the catalyst to fail. Summary of the Invention

[0004] Therefore, the purpose of this invention is to provide a three-layer core-shell structured oxygen evolution catalyst, its preparation method, and its application, to solve the problems of high precious metal usage and insufficient stability in current oxygen evolution catalysts used in PEM water electrolysis for hydrogen production. This invention utilizes a Pt and / or Au precious metal sub-outer layer to coat a non-precious metal core, which solves the problem of easy corrosion of the non-precious metal core. Furthermore, using the aforementioned precious metal-coated non-precious metal core as a support for highly reactive oxygen evolution materials can reduce the amount of precious metal Ir used. Since the sub-outer layer of Pt and / or Au is only a few atoms thick and used in extremely low quantities, the total amount of precious metal used in the catalyst is significantly reduced compared to unsupported commercial iridium oxide catalysts, and stability is also guaranteed.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] In one aspect, the present invention provides a three-layer core-shell structure oxygen evolution catalyst, wherein the core of the oxygen evolution catalyst is a non-noble transition metal, the second outermost layer is a dense noble metal with an atomic layer thickness, and the outermost layer is iridium hydroxyl oxide nanoparticles with high oxygen evolution activity.

[0007] Based on the above technical solution, the non-noble transition metal is one or more of Ti, Cu, Co, Ni, Cr, Ta, and Nb; the noble metal is one or two of Au and Pt.

[0008] Based on the above technical solution, the thickness of the sub-outer layer is further 1-10 atomic layers.

[0009] Based on the above technical solution, the iridium hydroxy oxide is in the form of nanoparticles (≤5 nanometers), which are dispersed and deposited on the sub-outer layer surface in the form of single particles, or covered on the sub-outer layer surface in the form of a nanofilm composed of nanoparticles.

[0010] Another aspect of the present invention provides a method for preparing the above-mentioned three-layer core-shell structured oxygen evolution catalyst, comprising the following steps:

[0011] 1) Dispersing transition metal nanoparticles in water to obtain a dispersion;

[0012] 2) The noble metal is deposited on the surface of the transition metal nanoparticles in the dispersion of step 1) as the outermost layer to obtain the first solid;

[0013] 3) Add the first solid to water and disperse it evenly to obtain the first dispersion;

[0014] 4) Preheat the first dispersion at 100-300℃ to obtain the second dispersion;

[0015] 5) Add the Ir precursor solution to the second dispersion and react at 100-300℃ for at least 1 hour to obtain the third dispersion;

[0016] 6) Separate the solids in the third dispersion to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0017] Based on the above technical solution, further, the concentration of the dispersion in step 1) is 0.1-10 mg / mL.

[0018] Based on the above technical solution, further, in step 2), the deposition method includes electrodeposition or galvanic displacement method.

[0019] Based on the above technical solution, further, in step 2), the conditions for the galvani replacement method are: replacement temperature of 60-100℃, replacement time of 3-48h, and molar ratio of noble metal to transition metal nanoparticles of 2:98-15:85.

[0020] Based on the above technical solution, further, in step 3), the dispersion includes ultrasonic dispersion and stirring dispersion.

[0021] Based on the above technical solution, further, in step 4), the preheating temperature is 100-200℃; the preheating time is at least 15 minutes.

[0022] Based on the above technical solution, further, in step 5), the Ir precursor solution is an aqueous solution of a soluble salt or soluble acid of Ir, preferably an aqueous solution of at least one of IrCl3, IrCl4, H2IrCl6, K2IrCl6, and (NH4)2IrCl6.

[0023] Based on the above technical solution, further, in step 5), the mass ratio of Ir in the Ir precursor solution to the solid in the second dispersion is 1:9-3:1.

[0024] Based on the above technical solution, further, in step 5), the reaction temperature is 100-200℃, and the reaction time is at least 6 hours, preferably at least 12 hours.

[0025] Based on the above technical solution, further, in step 5), the separation method includes filtration and centrifugation, and the separated solids are washed with water and dried to obtain a three-layer core-shell structure oxygen evolution catalyst.

[0026] The present invention also provides the application of the above-mentioned three-layer core-shell structured oxygen evolution catalyst in water electrolysis for hydrogen production.

[0027] Based on the above technical solution, the three-layer core-shell structure oxygen evolution catalyst is further used as an anode oxygen evolution catalyst.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The three-layer core-shell structure oxygen evolution catalyst of the present invention uses relatively inexpensive non-precious metals for the core, which can reduce the amount of precious metals used and help reduce the cost of oxygen evolution catalyst.

[0030] (2) The three-layer core-shell structure oxygen evolution catalyst of the present invention utilizes a very thin noble metal sub-outer layer to coat the core, which can protect the core elements from being dissolved and also provide a good electronic conduction pathway for the outermost oxygen evolution active components. This is beneficial to improving the activity of the oxygen evolution catalyst, reducing the electrolysis voltage, and thus reducing the operating cost of PEM electrolysis for hydrogen production.

[0031] (3) The three-layer core-shell structure oxygen evolution catalyst of the present invention has a mass activity that is several times that of commercial iridium oxide catalysts. While reducing the amount of precious metals used, it can also maintain long-term stability in harsh oxygen evolution corrosion environment. Therefore, it can provide a low-cost and long-life oxygen evolution catalyst solution for PEM water electrolysis to produce hydrogen. Attached Figure Description

[0032] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.

[0033] Figure 1 This is a transmission electron microscope image of the three-layer core-shell structured oxygen evolution catalyst prepared in Example 1.

[0034] Figure 2 This is a comparison of the OER polarization curves of the three-layer core-shell structure oxygen evolution catalyst prepared in Example 1 and the commercial iridium oxide catalyst in an O2-saturated 0.1M HClO4 solution.

[0035] Figure 3 This is a comparison of the chronopotential curves of the three-layer core-shell structure oxygen evolution catalyst prepared in Example 1 and the comparative catalyst prepared in Comparative Example 1 in N2-saturated 0.1M HClO4 solution. Detailed Implementation

[0036] The present invention will be described in detail below with reference to the embodiments. However, the implementation of the present invention is not limited thereto. Obviously, the embodiments described below are only some embodiments of the present invention. For those skilled in the art, other similar embodiments can be obtained without creative effort and all fall within the protection scope of the present invention.

[0037] Example 1

[0038] A method for preparing a three-layer core-shell structured catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0039] 1. Accurately weigh 10 mg of commercially available nano Ti powder and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0040] 2. After preheating the above dispersion at 80℃ for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Ti 5:95, and then carry out the displacement reaction at 80℃ for 12 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the Au-coated Ti core-shell structured carrier material.

[0041] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0042] 4. After preheating the above dispersion at 120℃ for 15 min, add the pre-prepared H2IrCl6 aqueous solution so that the mass ratio of Ir to the support is 1:9, and then react at 120℃ for 24 h.

[0043] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0044] Figure 1 This is a transmission electron microscope image of the three-layer core-shell structured oxygen evolution catalyst prepared in Example 1. As can be seen from the image, nano-iridium hydroxyoxide (≤5 nm) coats the support material.

[0045] Figure 2 This is a comparison of the OER polarization curves of the three-layer core-shell structured oxygen evolution catalyst prepared in Example 1 and the commercial iridium oxide catalyst (Johnson Metthey) in an O2-saturated 0.1M HClO4 solution. The test conditions were: ensuring the same catalyst loading (100 μg / cm³). 2 Linear scan polarization testing was performed at a linear scan rate of 5 mV / s, with a potential scan range of 800–1366 mV vs. SCE, in a forward scan. Figure 2 It is evident that the three-layer core-shell structured oxygen evolution catalyst prepared in this embodiment exhibits significantly higher mass activity than commercial iridium oxide, regardless of whether it is based on Ir or the noble metal (Au+Ir).

[0046] Figure 3 This is a comparison of the chronopotential curves of the three-layer core-shell structured oxygen evolution catalyst prepared in Example 1 and the comparative catalyst prepared in Comparative Example 1 in a N2-saturated 0.1M HClO4 solution. The test conditions were: ensuring the same catalyst loading (100 μg / cm³). 2 ), at 10mA / cm 2 Electrolysis was performed at a constant current density, and the change in potential over time was recorded. The cutoff potential was set to 1700 mV vs. SCE. Figure 3It is evident that the three-layer core-shell oxygen evolution catalyst prepared in Example 1 exhibited a very stable potential during the 150-hour constant current electrolysis test. In contrast, the catalyst prepared in Comparative Example 1 showed a potential increase starting at 10 hours during the less than 100-hour constant current electrolysis test, and nearly reached the cutoff potential within 60 hours. The chronopotential testing results indicate that without the protection of the outermost noble metal layer, the electrolytic stability of the core-shell catalyst using only non-noble metals as the core is far inferior to that of the three-layer core-shell oxygen evolution catalyst protected by the outermost noble metal layer.

[0047] Example 2

[0048] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0049] 1. Accurately weigh 10mg of commercially available nano-Cu powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0050] 2. After preheating the above dispersion at 60℃ for 15 min, add the pre-prepared H2PtCl6 aqueous solution to make the molar ratio of Pt to Cu 10:90, and then carry out the displacement reaction at 60℃ for 18 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the core-shell structured carrier material of Pt coated Cu.

[0051] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0052] 4. After preheating the above dispersion at 100℃ for 15 min, add the pre-prepared IrCl3 aqueous solution so that the mass ratio of Ir to the support is 1:4, and then react at 100℃ for 36 h.

[0053] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0054] Example 3

[0055] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0056] 1. Accurately weigh 10mg of commercially available nano-Co powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0057] 2. After preheating the above dispersion at 60℃ for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Co 15:85, and then carry out the displacement reaction at 60℃ for 24 h. After the reaction is completed, cool naturally to room temperature, wash with water to separate and obtain the Au-coated Co core-shell structured carrier material.

[0058] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then sonicate for 15 min.

[0059] 4. After preheating the above dispersion at 150℃ for 15 min, add the pre-prepared IrCl4 aqueous solution so that the mass ratio of Ir to the support is 3:7, and then react at 150℃ for 12 h.

[0060] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0061] Example 4

[0062] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0063] 1. Accurately weigh 10mg of commercially available nano Ni powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0064] 2. After preheating the above dispersion at 80℃ for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Ni 5:95, and then carry out the displacement reaction at 80℃ for 12 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the Au-coated Ni core-shell structured carrier material.

[0065] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0066] 4. After preheating the above dispersion at 160℃ for 15 min, add the pre-prepared K2IrCl6 aqueous solution so that the mass ratio of Ir to the support is 4:6, and then react at 160℃ for 12 h.

[0067] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0068] Example 5

[0069] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0070] 1. Accurately weigh 10 mg of commercially available nano Cr powder and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0071] 2. After preheating the above dispersion at 80℃ for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Cr 5:95, and then carry out the displacement reaction at 80℃ for 6 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the Au-coated Cr core-shell structured carrier material.

[0072] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0073] 4. After preheating the above dispersion at 180℃ for 15 min, add the pre-prepared K2IrCl6 aqueous solution so that the mass ratio of Ir to the support is 1:1, and then react at 180℃ for 12 h.

[0074] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0075] Example 6

[0076] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0077] 1. Accurately weigh 10 mg of commercially available nano-Ta powder and add it to 10 mL of deionized water, then ultrasonically disperse for 15 min;

[0078] 2. After preheating the above dispersion at 90℃ for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Ta 5:95, and then carry out the displacement reaction at 90℃ for 12 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the Au-coated Ta core-shell structured carrier material.

[0079] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0080] 4. After preheating the above dispersion at 190℃ for 15 min, add the pre-prepared (NH4)2IrCl6 aqueous solution so that the mass ratio of Ir to support is 6:4, and then react at 190℃ for 12 h.

[0081] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0082] Example 7

[0083] A method for preparing a three-layer core-shell structured oxygen evolution catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0084] 1. Accurately weigh 10 mg of commercially available nano Nb powder and add it to 10 mL of deionized water, then ultrasonically disperse for 15 min;

[0085] 2. After preheating the above dispersion at 95°C for 15 min, add the pre-prepared HAuCl4 aqueous solution to make the molar ratio of Au to Nb 5:95, and then carry out the displacement reaction at 95°C for 12 h; after the reaction is completed, cool naturally to room temperature, and wash with water to obtain the Au-coated Nb core-shell structured carrier material.

[0086] 3. Accurately weigh 5 mg of the above carrier material and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0087] 4. After preheating the above dispersion at 200℃ for 15 min, add the pre-prepared (NH4)2IrCl6 aqueous solution so that the mass ratio of Ir to support is 7:3, and then react at 200℃ for 12 h.

[0088] 5. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain a three-layer core-shell structured oxygen evolution catalyst.

[0089] Comparative Example 1:

[0090] A method for preparing a catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0091] 1. Accurately weigh 5 mg of commercially available nano Ti powder and add it to 5 mL of deionized water, then ultrasonically disperse for 15 min;

[0092] 2. After preheating the above dispersion at 120℃ for 15 min, add the pre-prepared H2IrCl6 aqueous solution so that the mass ratio of Ir to the carrier Ti powder is 1:9, and then react at 120℃ for 24 h.

[0093] 3. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain the control catalyst 1, which does not contain the precious metal sub-outer layer.

[0094] Comparative Example 2

[0095] A method for preparing a catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0096] 1. Accurately weigh 5mg of commercially available nano-Cu powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0097] 2. After preheating the above dispersion at 100℃ for 15 min, add the pre-prepared IrCl3 aqueous solution so that the mass ratio of Ir to the support is 1:4, and then react at 100℃ for 36 h.

[0098] 3. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, then centrifuged and washed four times with deionized water to obtain the control catalyst 2, which does not contain the precious metal sub-outer layer.

[0099] Comparative Example 3

[0100] A method for preparing a catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0101] 1. Accurately weigh 5mg of commercially available nano-Co powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0102] 2. After preheating the above dispersion at 150℃ for 15 min, add the pre-prepared IrCl4 aqueous solution so that the mass ratio of Ir to the support is 3:7, and then react at 150℃ for 12 h.

[0103] 3. After the reaction was completed, the mixture was naturally cooled to room temperature, then centrifuged, and then washed four times with deionized water to obtain the comparative catalyst 3, which does not contain the precious metal sub-outer layer.

[0104] Comparative Example 4

[0105] A method for preparing a catalyst for hydrogen production by water electrolysis mainly includes the following steps:

[0106] 1. Accurately weigh 5mg of commercially available nano Ni powder and add it to 5mL of deionized water, then ultrasonically disperse for 15min;

[0107] 2. After preheating the above dispersion at 160℃ for 15 min, add the pre-prepared K2IrCl6 aqueous solution so that the mass ratio of Ir to the support is 4:6, and then react at 160℃ for 12 h.

[0108] 3. After the reaction was completed, the mixture was naturally cooled to room temperature, then centrifuged, and then washed four times with deionized water to obtain a comparative catalyst 4 without the precious metal sub-outer layer.

[0109] Table 1. Comparison of current densities at 1366 mV vs. SCE potential between the catalysts of Examples 1-7 and commercial iridium oxide.

[0110]

[0111]

[0112] Table 2 Comparison of oxygen evolution stability of catalysts in Examples 1-7 and Comparative Examples 1-4

[0113] Example 1 150 Example 2 90 Example 3 115 Example 4 95 Example 5 140 Example 6 145 Example 7 130 Comparative Example 1 55 Comparative Example 2 20 Comparative Example 3 14 Comparative Example 4 3

Claims

1. A three-layered core-shell structured oxygen evolution catalyst, characterized in that, The core of the oxygen evolution catalyst is a non-noble transition metal, the second outermost layer is a noble metal, and the outermost layer is iridium hydroxyoxide. The non-noble transition metal is one or more of Ti, Cu, Co, Ni, Cr, Ta, and Nb; the noble metal is one or two of Au and Pt. The thickness of the suboutermost layer is 1-10 atomic layers; The iridium hydroxyoxide is in the form of nanoparticles, ≤5 nanometers, which are dispersed and deposited on the sub-outer layer surface in the form of single particles, or covered on the sub-outer layer surface in the form of a nanofilm composed of nanoparticles.

2. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 1, characterized in that, Includes the following steps: 1) Dispersing transition metal nanoparticles in water to obtain a dispersion; 2) The noble metal is deposited on the surface of the transition metal nanoparticles in the dispersion of step 1) as the outermost layer to obtain the first solid; 3) Add the first solid to water and disperse it evenly to obtain the first dispersion; 4) Preheat the first dispersion at 100-300℃ to obtain the second dispersion; 5) Add the Ir precursor solution to the second dispersion and react at 100-300℃ for at least 1 hour to obtain the third dispersion; 6) Separate the solids in the third dispersion to obtain a three-layer core-shell structured oxygen evolution catalyst.

3. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 2, characterized in that, In step 2), the deposition method includes electrodeposition or galvanic displacement.

4. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 3, characterized in that, In step 2), the conditions for the galvani substitution method are: substitution temperature of 60-100℃, substitution time of 3-48h, and molar ratio of noble metal to transition metal nanoparticles of 2:98-15:

85.

5. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 2, characterized in that, In step 4), the preheating temperature is 100-200℃; the preheating time is at least 15 minutes.

6. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 2, characterized in that, In step 5), the Ir precursor solution is an aqueous solution of a soluble salt or soluble acid of Ir; the mass ratio of Ir in the Ir precursor solution to the solid in the second dispersion is 1:9-3:

1.

7. The method for preparing the three-layer core-shell structured oxygen evolution catalyst according to claim 2, characterized in that, In step 5), the reaction temperature is 100-200℃ and the reaction time is at least 6 hours.

8. The application of the three-layer core-shell structure oxygen evolution catalyst as described in claim 1 in the electrolysis of water to produce hydrogen.

9. The application according to claim 8, characterized in that, The aforementioned three-layer core-shell structured oxygen evolution catalyst is used as an anode oxygen evolution catalyst.

Citation Information

Patent Citations

  • Catalyst particle for solid polymer fuel cells, catalyst arranged by use thereof, and solid polymer fuel cell

    JP2015219947A

  • Coating and method for producing core shell nanoparticles

    WO2023285568A2